2014
DOI: 10.1002/pd.4447
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal findings in five cases of Fryns syndrome

Abstract: What's already known about this topic?Fryns syndrome is characterized by congenital diaphragmatic hernia, facial dysmorphisms, distal digital hypoplasia, and variable cerebral, ocular, cardiovascular, and genitourinary malformations. It is often lethal. No causative gene is known, and the diagnosis is based on clinical findings. Data on prenatal diagnosis are lacking. What does this study add?This study demonstrates that prenatal diagnosis of Fryns syndrome is currently not possible in most cases.This finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Neither facial dysmorphism (other than cleft lip) nor digital hypoplasia were visualized on ultrasound (latest scan at 17 weeks' gestation). However, a recent study comparing prenatal and postnatal findings in Fryns syndrome reported that neither facial dysmorphism nor distal digital hypoplasia can be reliably detected prenatally, while both can be readily appreciated postnatally [Peron et al., ]. As neither fetus underwent a post‐mortem or external examination, these particular phenotypic features cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Neither facial dysmorphism (other than cleft lip) nor digital hypoplasia were visualized on ultrasound (latest scan at 17 weeks' gestation). However, a recent study comparing prenatal and postnatal findings in Fryns syndrome reported that neither facial dysmorphism nor distal digital hypoplasia can be reliably detected prenatally, while both can be readily appreciated postnatally [Peron et al., ]. As neither fetus underwent a post‐mortem or external examination, these particular phenotypic features cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The postnatal survival rate is estimated at only 14–16%. Survivors have severe developmental delay and seizures …”
Section: Glossarymentioning
confidence: 99%
“…CNS: Variety of cerebral malformations including ventriculomegaly, callosal agenesis, gray matter heterotopias, and vermian hypoplasia . Polymicrogyria and absent olfactory bulbs in rare cases …”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations